2022
DOI: 10.3390/metabo12020172
|View full text |Cite
|
Sign up to set email alerts
|

Native Microbiome Members of C. elegans Act Synergistically in Biosynthesis of Pyridoxal 5′-Phosphate

Abstract: The roles of the healthy microbiome on the host and the relationships between members of the microbiome remain to be fully characterized. Due to the complexity of the interactions between the mammalian microbiome and its host, the use of model organisms such as the nematode worm Caenorhabditis elegans is a promising strategy to study host-microbiome interactions in vivo, as well as bacterial crosstalk within the host. Previously it was found that native bacterial isolates of the worm, Chryseobacterium sp. CHNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…12022 MYb131 and demonstrated the greatest maximum increase in lifespan with Chryseobacterium sp. CHNTR56 MYb120 [ 26 ]. We demonstrated that the native microbiome member Chryseobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…12022 MYb131 and demonstrated the greatest maximum increase in lifespan with Chryseobacterium sp. CHNTR56 MYb120 [ 26 ]. We demonstrated that the native microbiome member Chryseobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…For our study, the C. elegans CF512 (rrf-3; fem-1) strain was used, which are sterile at 25 °C, making them better-suited for lifespan-based experiments [ 27 ]. CF512 worms maintained at 21 °C were synchronized to segregate eggs from adult worms [ 26 ]. Briefly, 16.6% alkaline bleach ( v / v ) was used to kill the adult worms in addition to sanitizing them.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations